C-FLEX Advanced Finite Element Analysis Program for Flexible Pavement Analysis and Design. Issue 9 (September 2021) - Luo, Jiayi; Huang, Haohang; Qamhia, Issam I. A.; Tutumluer, Erol; Tingle, Jeb S.
The U.S. Army Engineer Research and Development Center (ERDC) of the U.S. Army Corps of Engineers has initiated an effort to modernize the Department of Defense (DOD) pavement design and evaluation procedures initially developed in the 1950s. Flexible pavement analyses and evaluations are currently performed based on the elastic layered WESLEA and WESDEF software programs. To modernize the current pavement design and evaluation procedures used by the DOD, an advanced axisymmetric Finite Element Method (FEM) based analysis program, named C-FLEX, was developed and is introduced in this paper. The C-FLEX program is designed to feature accurate material models for all pavement layers with the capability to model the cross-anisotropic and nonlinear elastic properties of unbound base/subbase and subgrade layers, the viscoelastic behavior of the asphalt mixture, as well as mechanical reinforcement using geosynthetics in flexible pavements. The FEM formulation in C-FLEX and the program architecture and implementation details are introduced and discussed in this paper. The different analysis schemes and proper models used to characterize the cross-anisotropy and stress-dependent material nonlinearity are also described in detail. The viscoelastic analysis scheme and the geosynthetic characterization are currently under development and so are not included in this paper. Furthermore, two conventional flexible pavements with different layer properties are analyzed to verify the solutions and reliability of the C-FLEX program. Based on this development effort with ERDC, the C-FLEX program is envisioned to eventually serve as the flexible pavement analysis engine for the DOD's new mechanistic design and evaluation platform.